Study and Evaluation of Rock Wool Board by using PVA/PU as a Polymer Blend Binder - Mohammed, Moayad Abdullah; Jaber, Mohammed Ali; Al-Maamouri, Abbas Fadel Essa (Iraqi Journal of Science, 2022)
The Rock Wool Board (RWB) is widely used in the building exterior insulation all over world. As polymer affects hardening of plate, meaning it acted as a basic binder in this work and gave a smooth texture, ease of carrying and workmanship in different sizes and shapes. PVA was studied at the rates of PVA %4, %5, %6.66, %10, %20, results showed that 6.66% is the best percentage, through tensile and bending tests, this percentage was use with polyurethane with rates of PU 1, 0.5, 0.333, 0.25, 0.2 It is found that the ratio 0.333 is the best ratio to give good mechanical properties of bending, tensile and elongation. This percentage was fixed on different percentages of polymer (PU/PVA) as %2.5, %5, %10, %15, %20 and examinations were performed on these percentages and percentage %10 was best, this percentage was adopted. Another study in change of the rock wool with rates of %5, %7.5, %10, %12.5, where it was found that best percentage of the rock wool is 12.5% ​​after studying mechanical and physical properties.